Occupational cancer in developed countries - Blair, Aaron (BioMed Central, 2011)
ABSTRACT: Studies of occupational exposures have made major contributions to our understanding of human carcinogenesis. About one third of the factors identified as definite or probable human carcinogens were first investigated in the workplace and these exposures exact a considerable toll on working populations. There are many additional workplace exposures that are suspect carcinogens that require further evaluation to ensure a safe work environment. Information from occupational investigations is also relevant to the general population because many occupational exposures can be found outside the workplace. Much of our understanding about occupational cancer has been obtained from studies largely composed of white men in developed countries. The movement of industry from developed to developing countries underscores the need for future investigations to include more diverse populations.